Power factor improvement of distribution system with EV chargers based on SMC method for SVC - Farkoush S. (2017)
© The Korean Institute of Electrical Engineers. Utilization of Electric Vehicles (EVs) have been growing popularity in recent years due to increment in fuel price and lack of natural resources. Random unexpected charging by home EV charger in distribution is predicted in the future. The power quality problems such as fluctuation of power factor in a residential distribution network was explored with random EV chargers. This paper proposes a high-performance nonlinear sliding mode controller (SMC) for an EV charging system to compensate voltage distortions and to enhance the power factor against the unbalanced EV chargers. For the verification of the proposed scheme, MATLAB-Simulink simulations are performed on 22.9-kV grid. The results show that the proposed scheme can improve the power factor of a smart grid due to the EV chargers on the grid.